90Y TOF-PET based EUD reunifies patient survival prediction in resin and glass microspheres radioembolization of HCC tumours. (12th December 2018) - d'Abadie, P; Hesse, M; Jamar, F; Lhommel, R; Walrand, S
Abstract: Clinical studies reported a twofold ratio between the efficacies per Gy of resin versus glass spheres. Our aim is to investigate whether this difference could result from the different degrees of heterogeneity in sphere distribution between the two medical devices. The 90 Y TOF-PET based equivalent uniform doses (EUD) was used for this purpose. 58 consecutive HCC radioembolizations were retrospectively analyzed. Absorbed doses D and Jones–Hoban EUD in lesions were computed. Radioembolization efficacy was assessed using Kaplan–Meier survival curves. In order to match together the glass and resin spheres survival curves using a 40 Gy-threshold, an efficacy factor of 0.73 and 0.36 has to be applied on their absorbed dose, respectively. Using EUD, a nice matching between glass and resin survival curves was obtained with a better separation of the responding and not responding survival curves. The results clearly support the fact that the activity heterogeneity observed in 90 Y TOF-PET post radioembolization does not only result from statistical noise, but also reflects the actual heterogeneity of the spheres distribution. Use of EUD reunifies the efficacy of the two medical devices.